Percutaneous closure of the coronary artery-pulmonary artery fistula in a patient with apical hypertrophic cardiomyopathy [Apikal hipertrofik kardiyomiyopatili bir hastada koroner arter ile pulmoner arter arasindaki fistülün perkütan yolla kapatilmasi] - MUTLU, BÜLENT; SÜNBÜL, MURAT (Turkish Anaesthesiology and Intensive Care Society, 2013)
A fifty-four-year-old female patient was admitted to our unit with exertional chest pain of six months duration. Transthoracic echocardiography showed apical hypertrophy. Upon further investigation, cardiac magnetic resonance imaging revealed apical hypertrophic cardiomyopathy. The patient underwent myocardial perfusion scintigraphy which showed anterior ischemia. Coronary angiography revealed an arteriovenous fistula (AVF) from the left anterior descending artery to the pulmonary artery. The patient's chest pain was attributed to a coronary steal syndrome secondary to the coronary AVF. The AVF fistula was closed with a coil and the patient's chest pain improved. In conclusion, coronary steal syndrome may lead to myocardial ischemia in patients with a coronary AVF. © 2013 Türk Kardiyoloji Derneǧi.
Keywords: Arteriovenous fistula/epidemiology; Chest pain; Coronary angiography; Coronary vessel anomalies; Coronary-subclavian steal syndrome